КРИВИЦА И КАЗНА: ИСЛЕЂИВАЊЕ У ДЕЛУ ФРАНЦА КАФКЕ (Philological Studies, 2019)
This paper’s subject is the motif of judicial investigation in Franz Kafka’s narrative opus, primarily in his novels The Trial (Der Process) and The Castle (Das Schloss) and in certain short stories (The Judgment, In the Penal Colony, The Burrow, The Problem of Our Laws). The paper focuses on those elements of the judicial investigation process that appear in Kafka’s work in an exceptional manner and can’t be identified with classic treatments of that subject, such as those in Orwell’s 1984 or Dostoyevsky’s paradigmatic The Brothers Karamazov (Братья Карамазовы). Particular attention is dedicated to typical investigation elements such as the relationship of authority and conscience, knowledge and guilt, secrecy of the court’s activities, rituality of the process and bureaucracy, and the author highlights what constitutes their particularity in Kafka’s interpretation. Perceived like that, the commonplaces of the judicial process in Kafka’s work have often served as a basis for political and theological readings of his work; on that account, this paper questions the thesis that Kafka is a political writer. Among those commonplaces, the paper highlights guilt, monopolization of knowledge, the secrecy and inscrutability of the law’s appliance, the court’s actions and the importance of the process, but the bureaucratic apparatus as well, as the fundamental indicator of the process’s omnipotence and the omnipresence of guilt. The influence of historical inquisition and its rituality on the depictions of investigation and punishment in Kafka are underlined as well. The absence of rebellion and rebellious characters is a commonplace in his work, and the concept of predestined guilt and the idea of the rebellion’s futility is mirrored on the linguistic level, in a literal use of metaphor and the language of Kafka’s works in general.
Keywords: Franz Kafka, judicial investigation, bureaucracy, agnosticism, knowledge and faith, guilt and punishment, monopolization of knowledge, secrecy of the law, the court and the process, rituality, human-function